The structural temperature of water and the formation of marine aerosols (physico-chemical analysis) - Kushnir, S.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The analysis of physico-chemical processes that lead to the formation of marine aerosols is performed. On the basis of new data, the scheme of 4-stage changes in the molecular structure of water at the heating is substantiated. For cold water, the cluster-polymer structure is given in detail. It is shown that the interface boundary with air has a much higher structural temperature, which takes its water from state I to state II, which is characteristic of bulk water at 100—220 °C. It is shown that, at the barbotage of passive gases through solutions of salts in water I, the structural temperature of the solution substantially increases, which leads to a decrease of the solubility of gases and an increases of the chemical activity of water and dissolved oxygen. A new model of formation of a charged acidic aerosol of negatively charged air bubbles is proposed.